Okrucieństwo wobec zwierząt z punktu widzenia psychologii i filozofii — zarys problemu - Helios, Joanna; Jedlecka, Wioletta (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The issue of animal rights is one of the most important problems facing society today. Topicality and relevance of topics covered in relation to the protection of animals are not in doubt, which still remind lively discussions on the rights of animals. In our opinion, the discourse about animals and their rights plays essential role in the issue of animal cruelty. This article focuses on the psychological and philosophical aspects of animal cruelty.
Keywords: okrucieństwo wobec zwierząt; aspekty psychologiczne; aspekty filozoficzne